Subject scheduling system using Ant Colony Optimization at MAN 3 Palembang - Al Ashri, Muhammad Rizky; Miraswan, Kanda Januar; Darmawahyuni, Annisa; Utari, Meylani (Fakultas Ilmu Komputer Universitas Sriwijaya, 2024)
In preparing the subject schedule, it must be done correctly because all teaching and learning activities are between teachers and students. So far, the subject scheduling process at MAN 3 Palembang is carried out manually so that clashes often occur between subjects and teachers who teach can teach in different classes at the same time resulting in the teaching and learning process being slightly disrupted. One of the common metaheuristic algorithms The solution used for optimization problems is the Ant Colony Optimization algorithm or commonly known as the ant algorithm. The application system or users of this application to create schedules using the Ant Colony Optimization algorithm method is useful for operators who create schedules in schools. This system can also be applied in cases where schedules conflict, namely teachers teaching in the same room and teachers teaching the same subject teaching in different classes at the same hours. This makes it easier for operators to create schedules so that they can be resolved more easily and quickly. This application was successfully developed into a subject scheduling system and managed to run optimally. From the results of implementing scheduling using the Ant Colony Optimization algorithm method used in compiling subject rosters, it can help the MAN 3 Palembang school which previously carried out schedule preparation manually.